2018
DOI: 10.1186/s40659-018-0192-5
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of NCAPG, KNL1, miR-148a-3p, miR-193b-3p, and miR-1179 may contribute to the progression of gastric cancer

Abstract: BackgroundEmerging evidence indicate that miRNAs play an important role on gastric cancer (GC) progression via regulating several downstream targets, but it is still partially uncovered. This study aimed to explore the molecular mechanisms of GC by comprehensive analysis of mRNAs and miRNA expression profiles.MethodsThe mRNA and miRNA expression profiles of GSE79973 and GSE67354 downloaded from Gene Expression Omnibus were used to analyze the differentially expressed genes (DEGs) and DE-miRNAs among GC tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 43 publications
4
51
0
Order By: Relevance
“…[19][20][21] Several miRNAs have been identified as being associated with different cancers, including OS, 22,23 and there is evidence that miR-193b acts as a tumor suppressor in various types of cancer. [24][25][26][27][28][29][30] In the present study, we demonstrated that miR-193b expression is lower in OS specimens than in adjacent normal tissue. To better characterize the role of miR-193b, we then conducted functional studies, and showed that miR-193b overexpression induces apoptosis in OS cells, while miR-193b knockdown yields the opposite effect in vitro.…”
Section: Discussionmentioning
confidence: 78%
“…[19][20][21] Several miRNAs have been identified as being associated with different cancers, including OS, 22,23 and there is evidence that miR-193b acts as a tumor suppressor in various types of cancer. [24][25][26][27][28][29][30] In the present study, we demonstrated that miR-193b expression is lower in OS specimens than in adjacent normal tissue. To better characterize the role of miR-193b, we then conducted functional studies, and showed that miR-193b overexpression induces apoptosis in OS cells, while miR-193b knockdown yields the opposite effect in vitro.…”
Section: Discussionmentioning
confidence: 78%
“…MCPH gene overexpression is always associated with centriole overduplication, multipolar spindles, anaphase-lagging chromosomes, and micronuclei. MCPH4, MCPH7, MCPH8, MCPH10, MCPH13, MCPH17, MCPH19, and MCPH23 are highly expressed in different tumor tissues or cancer cell lines, indicating that some MCPH genes can be considered as oncogenes or potential cancer biomarkers [24][25][26][27][28][29][30][31]. The knockdown or inhibited expression of these genes may be a potential therapeutic method for cancer treatment [31][32][33].…”
Section: Some Mcph Genes Can Be Considered As Potential Cancer Biomarmentioning
confidence: 99%
“…Reduced neurons and neural progenitors, premature cell cycle exit, and increased cell death [49] N/A (Leukemia) [50] Premature neuronal differentiation [51] Nuclear division of cells (GC) [27] MCPH5 (ASPM)…”
Section: Mcph3 (Cdk5rap2)mentioning
confidence: 99%
See 2 more Smart Citations